Common variation at 3p22.1 and 7p15.3 influences multiple myeloma risk - Broderick, Peter; Chubb, Daniel; Johnson, David C; Weinhold, Niels; Försti, Asta; Lloyd, Amy; Olver, Bianca; Ma, Yussanne P; Dobbins, Sara E; Walker, Brian A; Davies, Faith E; Gregory, Walter A; et al. (Nature genetics, 2012)
Richard Houlston, Gareth Morgan, Kari Hemminki and colleagues report the results of a genome-wide association study of multiple myeloma. They identify two regions influencing susceptibility to this hematological malignancy. To identify risk variants for multiple myeloma, we conducted a genome-wide association study of 1,675 individuals with multiple myeloma and 5,903 control subjects. We identified risk loci for multiple myeloma at 3p22.1 (rs1052501 in ULK4 ; odds ratio (OR) = 1.32; P = 7.47 × 10 −9 ) and 7p15.3 (rs4487645, OR = 1.38; P = 3.33 × 10 −15 ). In addition, we observed a promising association at 2p23.3 (rs6746082, OR = 1.29; P = 1.22 × 10 −7 ). Our study identifies new genomic regions associated with multiple myeloma risk that may lead to new etiological insights.